Dilema Generasi Z: Antara Patriotisme dan Godaan Produk Asing - Rizki, Hafidh; Sasongko, Rolan Mart; Saraswati, Yudhistira; Balqis, Fadhila (EKONOMI DAN BISNIS DIGITAL, 2024)
This abstract presents findings on the dilemma faced by Generation Z in Indonesia, who are torn between maintaining patriotism and loyalty to local products, and the strong allure of foreign products promoted through social media. This study aims to examine the extent to which the phenomenon of "Fear of Missing Out" (FoMO) and patriotism influence the purchase intentions of Generation Z students at Universitas Pembangunan Nasional "Veteran" Yogyakarta. Using a Structural Equation Modeling (SEM) approach, the results indicate that both patriotism and FoMO play a significant role in shaping the intention to purchase local products, although FoMO does not function as a mediator. These findings are essential for policymakers and business practitioners to develop smart marketing strategies, combining FoMO elements and enhancing patriotic sentiments to boost preference for local products. This provides new insights into efforts to promote domestic product consumption amidst the challenges of globalization and the penetration of foreign products.Indonesia's